Feasibility of Democratisation in Sub-Sahara Africa, A study of South Africa after Apartheid system - Saka, Moshood (President University, 2020)
This article explores the intellectual ideas of Ake on feasibility of democratisation in Africa. Democratisation is feasible as government focuses on the real people irrespective of racial affinity. In the past, the apartheid government in South Africa was adjudged as obstacle to democracy because majority black were marginalised in the representative democracy. The African National Congress (ANC) developed a pressure against undemocratic laws of apartheid rule. This process translated to Trust Reconciliation Commission (TRC) as a driving-mechanism towards peaceful negotiation in the country. While this is true, this article argues that transition to democratisation in 1994 by founding elections marked the beginning of a representative government. This article contests the current practice of democratisation by political disconnection of the popular party after the death of President Nelson Mandela. Finally, it is argued that feasibility of democracy is economic empowerment of the people but was trivialised in the country. The article further states the characters which marred democratisation process after the post-third wave. The article submits that there was adequate oversight functions which checked the excess power of executive arm and the others. This de facto is justified by the action of opposition parties such as EFF, DA, and IFP in the Freedom House. As a result, triangulation politics is recommended as mechanism which can promote national unity in the country.